In memoriam Edo Fimmen, General Secretary of the ITF : 18 June - 14 December 1942. (London : ITF, 1942)
Themanummer van The International Transport Workers' Journal, 03(1942) 11/12
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Fimmen, Edo